2,4-Di-Tert-Butylphenol Isolated From an Endophytic Fungus, Daldinia eschscholtzii, Reduces Virulence and Quorum Sensing in Pseudomonas aeruginosa - Mishra, Rashmi; Kushveer, Jai Shanti; Khan, Mohd. Imran K.; Pagal, Sudhakar; Meena, Chetan Kumar; Murali, Ayaluru; Dhayalan, Arunkumar; Venkateswara Sarma, Vemuri (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is among the top three gram-negative bacteria according to the WHO’s critical priority list of pathogens against which newer antibiotics are urgently needed and considered a global threat due to multiple drug resistance. This situation demands unconventional antimicrobial strategies such as the inhibition of quorum sensing to alleviate the manifestation of classical resistance mechanisms. Here, we report 2,4-Di-tert-butyl phenol (2,4-DBP), isolated from an endophytic fungus, Daldinia eschscholtzii inhibits the quorum sensing properties of P. aeruginosa. We have found that treating P. aeruginosa with 2,4-DBP substantially reduced the secretion of virulence factors as well as biofilm, and its associated factors that are controlled by quorum sensing, in a dose-dependent manner. Concomitantly, 2,4-DBP also significantly reduced the expression of quorum sensing related genes i.e., lasI, lasR, rhlI, rhlR significantly. Importantly, 2,4-DBP restricted the adhesion and invasion of P. aeruginosa to the A549 lung alveolar carcinoma cells. In addition, bactericidal assay with 2,4-DBP exhibited synergism with ampicillin to kill P. aeruginosa. Furthermore, our computational studies predicted that 2,4-DBP could bind to the P. aeruginosa quorum sensing receptors LasR and RhlR. Collectively, these data suggest that 2,4-DBP can be exploited as a standalone drug, or in combination with antibiotic(s) as an anti-virulence and anti-biofilm agent to combat the multi-drug resistant P. aeruginosa infection.